2021
DOI: 10.1002/anie.202108599
|View full text |Cite
|
Sign up to set email alerts
|

P‐Block Atomically Dispersed Antimony Catalyst for Highly Efficient Oxygen Reduction Reaction

Abstract: Main‐group (s‐ and p‐block) metals are generally regarded as catalytically inactive due to the delocalized s/p‐band. Herein, we successfully synthesized a p‐block antimony single‐atom catalyst (Sb SAC) with the Sb−N4 configuration for efficient catalysis of the oxygen reduction reaction (ORR). The obtained Sb SAC exhibits superior ORR activity with a half‐wave potential of 0.86 V and excellent stability, which outperforms most transition‐metal (TM, d‐block) based SACs and commercial Pt/C. In addition, it prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 31 publications
0
82
0
Order By: Relevance
“…This charge transfer makes Sn–N 4 a highly polar site for the polysulfide adsorption because the positive Sn atom can account for the S x anion binding site and the electron-rich ligand atoms can act as the Lewis base to form a bond with lithium. 45,56…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This charge transfer makes Sn–N 4 a highly polar site for the polysulfide adsorption because the positive Sn atom can account for the S x anion binding site and the electron-rich ligand atoms can act as the Lewis base to form a bond with lithium. 45,56…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports, the SACs employed in Li–S batteries were all based on d-block transition metals, in which the partially filled d bands are the origin of the electrocatalysis activities. 45 Compared with the d-block transition metal elements, the p-block elements show outstanding stability due to the poor electronic flexibility. 46 Surface engineering, like the N-doped carbon supported single p-block metal atom materials, offers a wealth of pathways for activating p-block materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of electrons around O implied that O captures more electrons from Zn compared with N attributed to the stronger electronegativity of O. [26] Moreover, compared with ZnN 4 , it was observed that the d-band center of ZnO 3 C downshifts away from the Fermi level (Figure 4 c), which would definitely affect the adsorption strength between oxygenated intermediates and metal active sites (Figure S18). [27] The free energy diagram of 2 e À /4 e À ORR pathway intermediates on ZnO 3 C and ZnN 4 at 0 V is displayed in Figure 4 d and Tables S8 and S9.…”
Section: Methodsmentioning
confidence: 99%